First World War and a Vision of Global Chaos and Decay: An Analysis of D. H. Lawrence’s Post-War Novels - Shakoor, Abdul; Shah, Ayaz Muhammad; Ullah, Azim (Annals of Human and Social Sciences, 2025)
The present research aims to explore a vision of global chaos and decay in Lawrence’s post-war novels. A careful comparison of Lawrence’s early and later novels shows that his pre-war novels reflect his zest for life and blissful blindness to bitter social realities. However, the outbreak of the Great War (1914-18) made him realize inherent death wish and suicidal instincts in European culture and this bitter realization of modern anti-life filled him with disgust for the European culture which is reflected in his post-war novels. The present research has adopted a qualitative method for the collection and analysis of the relevant data. The analysis proves that there is a marked difference between Lawrence’s pre-war and post-war novels. Later novels are full of imagery associated with decay, death, impotency and rottenness representing modern anti life. Future researchers can carry out other such research projects to explore the impact of war on various literary texts.